The economics of rating watchlists: Evidence from rating changes - Christian Hirsch; Christina E. Bannier (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
Generally, information provision and certification have been identified as the major economic functions of rating agencies. This paper analyzes whether the 'watchlist (rating review) instrument has extended the agencies' role towards a monitoring position, as proposed by Boot, Milbourn, and Schmeits (2006). Using a data set of Moody's rating history between 1982 and 2004, we find that the overall information content of rating action has indeed increased since the introduction of the watchlist procedure. Our findings suggest that rating reviews help to establish implicit monitoring contracts between agencies and borrowers and as such enable a finer partition of rating information, thereby contributing to a higher information quality.
urn:nbn:de:hebis:30-52376
Keywords: G14; G29; G33; 330; Credit Rating Agencies; Watchlist; Market Reactions; Event Study; Kreditwürdigkeit; Informationswert; Ratingagentur; Börsenkurs; Event Study; Welt